2017
DOI: 10.1163/22119434-00002065
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of stalk-eyed flies (Diptera, Diopsidae) in the Arabian Peninsula, with a review of cluster formation in the Diopsidae

Abstract: Catalogue and distribution data are presented for the six Diopsidae species known to occur in the Arabian Peninsula: Sphyracephala beccarii, Chaetodiopsis meigenii, Diasemopsis aethiopica, Diopsis arabica, Diopsis mayae and Diopsis sp. (ichneumonea species group). The biogeographical aspects of their distribution are discussed. Records of Diopsis apicalis and Diopsis collaris are removed from the list for Arabia as these were based on misidentifications. Synonymies involving Diasemopsis aethiopica and Diasemop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 21 publications
0
14
0
2
Order By: Relevance
“…A study on Stalk‐eyed flies infected with Laboulbeniales found infection rates up to 100% with long‐lived (univoltine) species, and much lower infection rates with short‐lived (multivoltine) species (Rossi & Feijen, 2018). A final factor that has been proposed as influencing the infection rate is aggregation behavior: Beetles and flies that group together for mating or overwintering are more likely to have higher infection rates (De Kesel, 1993; Feijen, Martin, & Feijen, 2017; Riddick & Schaefer, 2005). Bactrocera are all thought to be principally multivoltine (Drew & Romig, 2013), with the number of generations depending on the seasonal availability of fruit hosts.…”
Section: Discussionmentioning
confidence: 99%
“…A study on Stalk‐eyed flies infected with Laboulbeniales found infection rates up to 100% with long‐lived (univoltine) species, and much lower infection rates with short‐lived (multivoltine) species (Rossi & Feijen, 2018). A final factor that has been proposed as influencing the infection rate is aggregation behavior: Beetles and flies that group together for mating or overwintering are more likely to have higher infection rates (De Kesel, 1993; Feijen, Martin, & Feijen, 2017; Riddick & Schaefer, 2005). Bactrocera are all thought to be principally multivoltine (Drew & Romig, 2013), with the number of generations depending on the seasonal availability of fruit hosts.…”
Section: Discussionmentioning
confidence: 99%
“… Centrioncinae : Hennig, 1965: 62; Shillito 1971 : 288; Steyskal 1972 : 1; Feijen 1983 : 67 (as Centrioncidae ); Feijen 1989 : 115 [as Centrioncidae ]; McAlpine 1997 : 170; Hilger 2000 : 335; Meier and Hilger 2000 : 1, 6; Baker et al 2001 : 89; Meier and Baker 2002 : 332; Nartshuk 2003 : 246 [as Centrioncidae ]; De Meyer 2004 : 25; Kotrba and Balke 2006: 843; Kotrba et al 2010 : 299; McAlpine 2011 : 150; Feijen and Feijen 2021 : 1523. …”
Section: Taxonomyunclassified
“…These two families together were considered a possible sister-group of the Diopsidae . Feijen (1989) updated the diagnosis for the Centrioncidae .…”
Section: Introductionmentioning
confidence: 99%
“…Sphyracephala detrahens (Walker, 1860) belongs to the subfamily Diopsinae (Diptera: Diopsidae; Kotrba, 2004) and is distinguished by the possession of lateral projections from the sides of the head, where the compound eyes are located, in both sexes. Adult flies of most species of Diopsinae have been found in littoral areas and rainforests (Genus of Diopsis : Feijen, 1984; Feijen & Feijen, 2009; Feijen et al, 2021, Genus of Sphyracephala : Papp et al, 1997; Simova‐Tošić & Stojanović, 1999; Hauser et al, 2011; Stoaks & Shaw, 2011; Feijen et al, 2017, Genus of Teleopsis : Burkhardt, 1972; Feijen, 1998; Feijen & Feijen, 2011). With the exception of some pest species of rice, the habitats of diopsid flies during egg, larval, and pupal stages, and the feeding behaviours of their larvae in the field are poorly understood (Alam, 1988; Alghali & Osisanya, 1982; Feijen, 1979; Feijen, 1985).…”
Section: Introductionmentioning
confidence: 99%